DEVELOPMENT OF A RESOURCE CENTER FOR INCLUSIVE EDUCATION: ORGANIZATIONAL MODEL AND SUPPORT STRATEGIES IN CHAD - Ali Abakar Ben Abakar; Amrozi Khamidi; Ima Widiyanah (STKIP Pesisir Selatan, 2026)
Chad faces significant challenges in implementing inclusive education despite its commitment to the Convention on the Rights of Persons with Disabilities (CRPD) and Sustainable Development Goal 4 (SDG 4). Less than 5% of children with disabilities have access to formal education, highlighting the urgent need for effective support structures. This study aims to describe the current state of inclusive education in Chad, identify the main barriers to its implementation, and propose an organizational model for a Resource Center for Inclusive Education (RCIE). A descriptive-propositional qualitative approach was employed. Data were collected through 12 semi-structured online interviews involving teachers, school principals, Ministry of Education officials, families of children with disabilities, and civil society representatives in N'Djamena. Data were analyzed using Taguette software through thematic coding and categorization. The findings revealed four major categories of barriers: institutional, pedagogical, material, and sociocultural. Participants emphasized the need for teacher training, adapted educational resources, intersectoral coordination, and community awareness programs. Based on the IPOF framework and Self-Determination Theory, the study proposes eight organizational propositions for the development of an RCIE adapted to the Chadian context.